Virtualized Wireless Networks User Association and Resource Allocation - Le-Ngoc, Tho (SpringerBriefs in Electrical and Computer Engineering,, 2018)
There have been recent advancements in wireless network technologies such as wireless virtualization to accommodate the exponential growth in demand, as well as to increase energy and infrastructure efficiencies. This SpringerBrief discusses the user-association and resource-allocation aspects in Virtualized Wireless Networks (VWNs) and highlights key technology innovations to meet their requirements. Various issues in practical implementation of VWNs are discussed along with potential techniques such as Massive MIMO, Cloud-Radio Access Network (C-RAN), and non-orthogonal multiple access (NOMA). This SpringerBrief will target researchers and professionals working on current and next-generation wireless networks. The content is also valuable for advanced-level students interested in wireless communications and signal processing for communications.